Typing in Tandem: Language Planning in Multisentence Text Production Is Fundamentally Parallel. - Roeser, Jens; Conijn, Rianne; Chukharev, Evgeny; Ofstad, Gunn Helen; Torrance, Mark (Journal of Experimental Psychology. General, 2025)
Classical serial models view the process of producing a text as a chain of discrete pauses during which the next span of text is planned and bursts of activity during which this text is output onto the page or computer screen. In contrast, parallel models assume that by default planning of the next text unit is performed in parallel with previous execution. We instantiated these two views as Bayesian mixed-effects models across six sets of keystroke data from child and adult writers composing different types of multisentence text. We modeled interkey intervals with a single distribution, hypothesized by the serial processing account, and with a two-distribution mixture model that is hypothesized by the parallel processing account. We analyzed intervals occurring before sentence, before word, and within word. Model comparisons demonstrated strong evidence in favor of the parallel view across all data sets. When pausing occurred, sentence-initial interkeystroke intervals were longer than word-initial pauses. This is consistent with the idea that edges of larger linguistic units are associated with higher level planning. However, we found—across populations—that interkey intervals at word and even at sentence boundaries were often too brief to plausibly represent time to plan what was written next. Our results cannot be explained by the serial processing but are in line with the parallel view of multisentence text composition. Public Significance Statement: Competent writers often experience "flow" when composing text. Ideas seem to emerge from the fingers as you type. Our findings suggest that this results from a fundamental parallelism in how the mind plans and executes text.